P9 Does childhood socio-economic disadvantage moderate health behaviours and occupational and environmental hazards association's with adult lung function; a cross sectional analysis using the UK household longitudinal study. (September 2018) - Carney, C; Benzeval, M
Abstract : Background: Lung function is lower in people with disadvantaged socio-economic position (SEP) and is associated with certain health behaviours and exposures. The effects are likely to be interactive, for example socially patterned environmental tobacco smoke (ETS) in childhood is associated with an increased effect of smoking in adulthood. We hypothesise that disadvantaged childhood SEP increases susceptibility to the effect of hazards for lung function in adulthood. We test whether disadvantaged childhood SEP moderates smoking, physical activity, obesity, occupational exposures, ETS and air pollution's associations with lung function. Methods: Data are from the Nurse Health Assessment (NHA) in waves two and three of United Kingdom Household Longitudinal Study (UKHLS). The NHA is drawn from the UKHLS General Population Sample, a stratified, clustered, equal probability sample, and from the British Household Panel Survey sample which began in 1991 as a stratified random sample. Analysis is restricted to English residents aged at least 20 for women and 25 for men; an analytical sample of 16 328. Lung function is measured with forced expiratory volume in the first second (FEV1 ) and standardised to the percentage of expected FEV1 for a healthy non-smoker of equivalent age, gender, height and ethnicity (FEV1 %). A multilevel approach was used with individuals nested in households in neighbourhoods. Using STATA14, a mixed linear model was fitted with interaction terms between childhood SEP and health behaviours and occupational exposures. Cross level interactions tested whether childhood SEP moderated household ETS and neighbourhood air pollution's associations with FEV1 %. Results: SEP, smoking, physical activity, obesity, occupational exposures and air pollution were associated with lung function. Interaction terms indicated a stronger association between disadvantaged childhood SEP and currently smoking (coefficient (_b) −6.506%, 95% confidence intervals (95% CI): −9.561%, −3.451%), formerly smoking (_b −2.331% 95% CI −3.674%, −0.988%) and occupational exposures, (_b −1.436% 95% CI −2.725%, −0.147%). Significant interactions were not found with physical activity, obesity, ETS and air pollution. Conclusion: The findings suggest that disadvantaged SEP in childhood may make people more susceptible to the negative effect of smoking and occupational exposures in adulthood. This is important as those most likely to encounter these exposures are at greater risk to their effects. Policy to alleviate this inequality requires intervention in health behaviours and via health and safety legislation.